Topical Calendula officinalis L. successfully treated exfoliative cheilitis: A case report - Roveroni-Favaretto, Lúcia Helena Denardi [UNESP]; Lodi, Karina Bortolin [UNESP]; Almeida, Janete Dias [UNESP] (Springer Nature, 2009)
Authors describe a case of recurrent exfoliative cheilitis that responded to treatment with a standardized topical preparation of Calendula officinalis L. An eighteen-year-old man was referred to UNESP - São Paulo State University, Department of Biosciences and Oral Diagnosis, São José dos Campos Dental School to investigate a chronic dry scaling lesion on his lips. The patient's main chief was aesthetic compromising. Corticoid therapy was suspended and Calendula officinalis ointment 10% for ad libitum use has been prescribed. The results presented allow the authors to consider Calendula officinalis L. as a potential therapy in cases of cheilitis exfoliative. © 2009 Roveroni-Favaretto et al; licensee BioMed Central Ltd.
Keywords: herbaceous agent; sunscreen; triamcinolone; adult; breathing; case report; cheek mucosa; cheilitis; corticosteroid therapy; desquamation; dry skin; esthetics; exfoliative cheilitis; human; lip; male; marigold; mouth examination; oral breathing; recurrent disease